SPREADING OF A FLUID JET ON THE CORRUGATED SURFACE OF THE STRUCTURED PACKING OF WET SCRUBBERS - Gorodilov A.A.; Pushnov A.S.; Berengarten M.G. (Problems of the Regional Energetics)
The new packing for wet scrubbers for cooling exhaust gases of furnaces is presented. Spreading features of the fluid jet on the corrugated surface of the proposed packing have been studied. Flow rate of the liquid flowing through slits to the opposite side of the packing element was determined. Several regimes of a fluid flow on the surface of the proposed structured packing were determined. An optimal range of rational flow rates for more intense cooling of exhaust gases is proposed. It was discovered that the range of optimum flow rates may be extended if the surface of the packing element is pre-wetted. The way of increasing the rate of effective interfacial surface area for gas-liquid contact per unit volume of the packing of the scrubber is presented.